2010
DOI: 10.1016/j.mrfmmm.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of promoter methylation and gene expression endpoints between tumorous and non-tumorous tissues from HCV-positive patients with hepatocellular carcinoma

Abstract: Transcriptional silencing of tumor suppressor genes and other cancer-related genes induced by promoter CpG island hypermethylation is an important epigenetic mechanism of hepatocarcinogenesis. Previous studies have established methylation profiles of hepatocellular carcinomas (HCCs) and demonstrated that methylation of several candidate genes in resected tissues may be associated with time to recurrence. The goals of our study were to test whether specific promoter methylation and mRNA levels of candidate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In a series from Taiwan, hypermethylation was found in 39% HCC and there appeared to be a relationship between hypermethylation and aflatoxin B 1 DNA adducts [65]. However, other studies, including those from Japan, have found relatively low levels of MGMT hypermethylation in comparison to other target genes [66,67].…”
Section: Mgmtmentioning
confidence: 91%
“…In a series from Taiwan, hypermethylation was found in 39% HCC and there appeared to be a relationship between hypermethylation and aflatoxin B 1 DNA adducts [65]. However, other studies, including those from Japan, have found relatively low levels of MGMT hypermethylation in comparison to other target genes [66,67].…”
Section: Mgmtmentioning
confidence: 91%
“…Global DNA hypomethylation seems to occur in early neoplasia and has been regarded as an important component of cancer development (Das and Singal, 2004;Zhu et al, 2011). Compared with normal tissue counterparts, lower global DNA methylation was observed in tumor tissues in a broad panel of cancers including HCC (Das and Singal, 2004;Formeister et al, 2010). Animal studies have shown that experimentallyinduced hypomethylation can lead to cancer development at multiple sites (Wilson et al, 1984;Thomas and Williams, 1992;Gaudet et al, 2003), indicating the causal role of global DNA hypomethylation in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…HCV core genotype 1 has shown several oncogenic properties, such as the activation of STAT3 and its downstream molecules, c-myc and cyclin D [73], the suppression of the c-fos promoter [74] and the activation of the AMPK/ERK cascade, inducing cell cycle progression [75]. Besides these classical mechanisms, a link between HCV infection and the aberrant methylation levels of some HCC-related genes, namely p16/INK4A, SOCS1, RASSF1A, APC, GSTP1 and RIZ1, was already demonstrated [56,76]. Two in vitro studies reported hypermethylated levels of E-cadherin promoter in hepatocytes expressing the HCV core protein genotype 1b [18,77].…”
Section: Hcv and Dnmtsmentioning
confidence: 99%